Pengaruh Pembelajaran Multimedia terhadap Hasil Belajar Matematika - Yuan Andinny; Indah Lestari (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
The aim of this research is to determine the effect of instructional multimedia on students’ mathematics achievement in State Elementary School Jatirangga II Bekasi on material geometry. The method used in this study was quasy experiment. Data collection techniques performed by administering the test after treatment to determine the result of students’ mathematics achievement. Samples were taken by simple random sampling technique selected 46 students comprising 23 students as an experimental group and 23 students as the control group. The results of calculations using the data normality Liliefors shows that both the experimental and control group is normally distributed. While the results of the homogeneity test with fisher test of both the experimental group and control both the data has the same variant or homogeneous. Hypothesis Testing using  test which produces hitung > tabel. Then there is the significant  effect of instructional multimedia on students’ mathematics achievement in State Elementary School Jatirangga II Bekasi on material geometry.